2019
DOI: 10.1002/kjm2.12156
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of hematological and neurological expressed 1 (HN1) is associated with a poor prognosis of hepatocellular carcinoma and its knockdown inhibits cell growth and migration partly by down‐regulation of c‐Met

Abstract: Hematologic and neurological expression 1 (HN1) has been reported to involved in certain cancers, but its role in hepatocellular carcinoma (HCC) is largely unknown. The contribution of HN1 to HCC progression was investigated in the present study. We found that HN1 was significantly up‐regulated in HCC tissues, compared with normal tissues, by analyzing the Oncomine and Human Protein Atlas database; and found that high expression of HN1 was markedly associated with worse overall survival, relapse‐free survival,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…CircHN1 is formed by reverse splicing of the linear transcript of exons 3‐5 of HN1 gene. HN1 mRNA has been shown to be upregulated in certain cancers 21‐24 . Increased HN1 expression has been reported to upregulate c‐Met to promote cell growth and migration and is linked to a poor prognosis for patients with hepatocellular carcinoma (HCC) 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CircHN1 is formed by reverse splicing of the linear transcript of exons 3‐5 of HN1 gene. HN1 mRNA has been shown to be upregulated in certain cancers 21‐24 . Increased HN1 expression has been reported to upregulate c‐Met to promote cell growth and migration and is linked to a poor prognosis for patients with hepatocellular carcinoma (HCC) 21 .…”
Section: Discussionmentioning
confidence: 99%
“…HN1 mRNA has been shown to be upregulated in certain cancers 21‐24 . Increased HN1 expression has been reported to upregulate c‐Met to promote cell growth and migration and is linked to a poor prognosis for patients with hepatocellular carcinoma (HCC) 21 . In breast cancer, HN1 can enhance MYC expression to contribute to cancer progression 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al ( 16) have revealed that circ-DONSON is upregulated in tumor tissues and its knockdown restrains cell proliferation, migration, and invasion in GC. The expression of the HN1 gene is commonly elevated in tumors and contributes to accelerated tumor progression in breast cancer, anaplastic thyroid carcinoma, prostate cancer, and hepatocellular carcinoma (17)(18)(19)(20). CircHN1, encoded by the HN1 gene, can promote proliferation, migration, and invasion, as well as inhibit apoptosis in GC (11,12).…”
Section: Gsk3a Reversed the Effects Of Mir-485-5p On Gc Cell Progressionmentioning
confidence: 99%
“…289 HN1 was correlated with a poor prognosis in HCC patients. 290 Pu et al 291 294 Moreover, bioinformatic approaches and various databases have enabled the discovery of thousands of novel ncRNAs in cancers, including GI cancer. These databases include CRlncRNA, Lnc2Cancer, and LncRNADisease.…”
Section: Circrnas and Angiogenesis In Gi Cancersmentioning
confidence: 99%
“… 289 HN1 was correlated with a poor prognosis in HCC patients. 290 Pu et al. 291 investigated the hsa_circ_0000092 and HN1 effects on angiogenesis in HCC.…”
Section: Circrna Biogenesismentioning
confidence: 99%